Pengembangan Media Interaktif Aksara Jawa Berbasis Multimedia Terhadap Hasil Belajar - Surur, Agus Miftakus; Wulandari, Refi; Rofiah, Tutik Dinur; Triani, Dewi Agus (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
Learning to use print media makes learning monotonous because printed books are used daily, which makes some students not pay attention and are busy. This has an impact on the value of student learning outcomes. In fact, there are tools to develop media that are not utilized properly. By developing interactive media so that students are interested in learning and pay attention from the beginning to the end. The purpose of this study was to determine the practical feasibility and effectiveness of multimedia-based interactive media on grade 3 student learning outcomes. The type of research used was Research and Development (RnD), with the ADDIE research model, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used in this study were validation sheets, questionnaires, and student learning outcomes. In the instrument above, the results of expert validation were media expert 1 obtaining 80.00% and media expert 2 obtaining 86.66%. Material expert 1 gets 90.66% and material expert 2 gets 82.66%, so each of the validators is in the appropriate and very feasible category. From the results of the questionnaire assessment, it was determined that a small scale percentage of 96.17% and a large scale percentage of 88.27% belonged to the very decent category. Meanwhile, based on the value of students obtaining a percentage of 80% on a small scale and 95% on a large scale belonging to the very high category, this medium can be said to be effective.